Analisis Strategi Pemasaran Produk KPR iB dengan Akad Musyarakah Muttanaqishah (MMQ): Studi Pada PT Bank Frwrd.Tbk - Reza Triandharta; Marissa Grace Haque-Fawzi (Indonesia Banking School, 2018)
The rapid development of sharia banking industry in Indonesia is inseparably from the population of 80 percent of Indonesian Muslim community. The development of mortgage business in Indonesia experienced a period of ups and downs. Especially for sharia-based KPR or commonly called the KPR iB is required to be able to take advantage of a vast market in Indonesia. But in line with its development, the condition also triggers high level of competition among fellow financial institution in similar field. This prompted the banking sector to continue to innovate in developing KPR iB products that are easily accepted by many parties and in accordance with the principles of sharia. Coupled with the influence of uncontrollable external factors from outside Indonesia, spurred PT Bank FRWRD Tbk to continuously evaluate strategies and breakthroughs in order to survive and continue to develop, formulate new strategy forms, in order to improve the competitiveness of companies and winning superior. This research begins by analyzing the internal and external environmental conditions of the company. In analyzing used SWOT analysis method to weight the degree of importance of each actor and factor. From the IE Matrix test, obtained competitive position PT Bank FRWRD Tbk on quadrant or cell IV IE Matrix, with growth concentration strategy through horizontal integration. By looking at the position: (1) compete; (2) strength; (3) weaknesses; (4) opportunities; and (5) threats. In this case PT Bank FRWRD Tbk should use the strategy: (1) market penetration; (2) market development; and also (3) horizontal integration strategy in addition to creating creative innovations should also be done